Effect Of Various Soil Medium On Seed Germination Of Simmondsia Chinensis (Link) Schneider (Jojoba) Under In Vivo Conditions - RAMAN BALA,; J.S. LAURA, (International Journal of Pharma and Bio Sciences, 2015)
The present work was conducted to elucidate the effect of different soil mediums in various ratios on seed germination efficiency and growth of seedling of Simmondsia chinensis under in vivo conditions. The highest germination (94%) was recorded for seeds cultivated in S1 medium containing desert soil and Farm Yard Manure (FYM) (2:1) followed by S4 medium (90%) having desert soil, clay, FYM (1:1:2), S3 medium (76%) in 2:1:1 composition and then to S2 medium (65%) germination in (1:2:1) ratio. Although, S. chinensis display better growth in desert soil, clay and FYM (1:1:2) yet in vivo (nursery) conditions they could raise potentially into healthy plantlets for successful establishment in the field. The present investigation could be of immense significance in selecting the soil type for commercialisation of this crop and improving their production to meet the market demand.